Kajian Penyediaan Tanaman pada Beberapa Sentra Produksi dan Penggunaannya dalam Lanskap - Sonjaya, Muthia Pratiwi; Budiarti, Tati; Nasrullah, Nizar (Jurnal Lanskap Indonesia, 2025)
Landscape plant nurseries are propagation and growing areas for trees, shrubs, ground cover plants, vines, water plants and herbs that are associated with several stakeholders such as landscape consultants, maintenance companies, contractors, and ornamental plant sellers. Nurserymen play a crucial role in providing plants for landscape projects, but the limited visibility of some nurseries poses a challenge to the procurement process. To address this issue, it is necessary to conduct a study that maps the location of nurseries and creates a database in several landscape plant production centers to facilitate consumers in meeting their plant needs. The study aimed to inventory plant diversity, analyze procurement and marketing practices in various ornamental plant centers, and assess the impact of different aspects of nurseries on plant application. Conducted from November 2023 to March across 10 districts in Bogor, Cianjur, and Depok regency, the research used descriptive quantitative analysis and correlation analysis to identify relationships between various aspects of plant procurement to identify key aspect for nurseries development. The research findings indicate a considerable diversity of plants within the production centers, with a total of 805 varieties across 10 districts in Bogor, Cianjur, and Depok regency. Despite 76% of these production centers employing conventional procurement methods, they are sufficiently able to meet the plant needs of their users. The study recommends policy initiatives focusing on plant specifications and net pricing, establishing a real-time plant database, and mapping nursery distribution locations to enhance procurement efficiency, benefiting both consumers and producers.